Hot topics in governance for forests and trees: Towards a (just) transformative research agenda - Larson, A.M.; Mausch, K.; Bourne, M.; Luttrell, C.; Schoneveld, George C.; Cronkleton, P.; Locatelli, Bruno; Catacutan, D.; Cerutti, P.O.; Chomba, S.; Djoudi, H.; Ihalainen, Markus; et al. (Elsevier, 2021)
We are living in a time of crisis on planet Earth. Urgent calls for transformational change are getting louder. Technical solutions have an important role to play in addressing pressing global challenges, but alone they are not enough. After all, who decides what kind of transformation is needed, of what, and for whom? What principles guide those decisions, and how are decision-makers held accountable? This commentary article argues that these governance questions are central in any solution, in order to simultaneously address the planetary crises of forest and biodiversity loss and degradation and growing inequality. To this end, we examine governance in forests and around trees, in landscapes and on farms, through the lens of power and social justice. For applied research aimed at actionable solutions to these global problems, we propose a governance research agenda for the next decade that is both transformative and just.